Thermochromic Magnetic Ionic Liquids from Cationic Nickel(II) Complexes Exhibiting Intramolecular Coordination Equilibrium. Issue 4 (5th December 2016) - Lan, Xue; Mochida, Tomoyuki; Funasako, Yusuke; Takahashi, Kazuyuki; Sakurai, Takahiro; Ohta, Hitoshi
Abstract: Among the various thermochromic materials, liquid thermochromic materials are comparatively rare. To produce functional thermochromic liquids, we have designed ionic liquids based on cationic nickel complexes with ether side chains, [Ni(acac)(Me2 NC2 H4 NR 1 R 2 )]Tf2 N ([1 ]Tf2 N: R 1 =C3 H6 OEt, R 2 =Me; [2 ]Tf2 N: R 1 =C3 H6 OMe, R 2 =Me; [3 ]Tf2 N: R 1 =R 2 =C3 H6 OMe), where acac=acetylacetonate and Tf2 N=(F3 CSO2 )2 N − . The side chains (R 1, R 2 ) can moderately coordinate to the metal center, enabling temperature‐dependent coordination equilibria in the liquid state. [1 ]Tf2 N is a liquid at room temperature. [2 ]Tf2 N is obtained as a solid ( T m =352.7 K) but remains liquid at room temperature after melting. [3 ]Tf2 N is a solid with a high melting point ( T m =422.3 K). These salts display thermochromism in the liquid state, appearing red at high temperatures and orange, light‐blue, or bluish‐green at lower temperatures, and exhibiting concomitant changes in their magnetic properties. This phenomenon is based on temperature‐dependent equilibrium between a square‐planar diamagnetic species and a paramagnetic species with intramolecular ether coordination. Abstract : Thermochromic magnetic ionic liquids : Thermochromic liquids have been designed based on cationic metal‐chelate complexes. These liquids exhibit color changes between red at high temperatures and orange, blue, or blue‐green at lower temperatures, depending on the cation. This phenomenon is based on temperature‐dependent coordination equilibria (see figure). The thermochromism is accompanied by changes in the magnetic properties.